Leaf structure of species of the Brassicaceae Burnett family in Southwestern Kyzylkum, Uzbekistan - Gulbahar Tursinbayeva; Abdiraxman Saparov; Alfiya Turekeeva; Kuralbay Atanazarov; Gayrat Matrasulov; Sherzod E. Sindarov; Durdona M. Alikarieva; Rustam Gulomov; Sokhiba I. Khudayorova; Bakayev Ziyovuddin; Ashurjon T. Mardanova (Caspian Journal of Environmental Sciences)
Leaf species of the family Brassicaceae have been studied, diagnostic features have been identified. Omitted by various types of trichomes: stellate, dendroid stomata are randomly arranged, numerous, non-submerged, mostly anomatid hemiparacytic anisocytic